2002
DOI: 10.1097/00042737-200204000-00023
|View full text |Cite
|
Sign up to set email alerts
|

A case of pancreaticoduodenal artery aneurysm causing pancreatic pseudotumour and duodenal obstruction

Abstract: This case report describes a ruptured pancreaticoduodenal artery aneurysm (PDAA) causing pancreatic pseudotumour and duodenal obstruction. A 59-year-old man was referred to our hospital with a chief complaint of frequent vomiting without abdominal pain. Because a mass lesion 10 cm in diameter was palpated in the right para-umbilical region and found in the head of the pancreas on computerized tomography (CT) and ultrasonography, malignant tumour of the pancreas or tumour-forming pancreatitis was strongly suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…10 Itoh et al reported a case of PDA aneurysm causing pancreatic pseudotumor and duodenal obstruction, which on angiography was an aneurysm of 8 mm in diameter, found in the posterior superior PDA. 11 Androulakakis et al reported a case of a gastric outlet obstruction caused by giant gastroduodenal artery aneurysm. 12 Chiou et al reported a case of pancreaticoduodenal artery aneurysm that began with intestinal angina and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…10 Itoh et al reported a case of PDA aneurysm causing pancreatic pseudotumor and duodenal obstruction, which on angiography was an aneurysm of 8 mm in diameter, found in the posterior superior PDA. 11 Androulakakis et al reported a case of a gastric outlet obstruction caused by giant gastroduodenal artery aneurysm. 12 Chiou et al reported a case of pancreaticoduodenal artery aneurysm that began with intestinal angina and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Another case presented with an incarcerated inguinal hernia that subsequently hemorrhaged into the retroperitoneum from a ruptured PDA aneurysm 10. Itoh et al reported a case of PDA aneurysm causing pancreatic pseudotumor and duodenal obstruction, which on angiography was an aneurysm of 8 mm in diameter, found in the posterior superior PDA 11. Androulakakis et al reported a case of a gastric outlet obstruction caused by giant gastroduodenal artery aneurysm 12.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported that transcatheter arterial embolization is effective in the treatment of visceral aneurysms, has few complications, and results in low recurrence rates [3][4][6][7][8][9]. Coll et al [3] reported that, since 1980, the mortality rate associated with surgery has been 19%, whereas that associated with transcatheter arterial embolization has been 0%; they reported no significant difference in the risk of recurrent hemorrhage, with rates between 0% and 5%.…”
Section: Discussionmentioning
confidence: 99%